Estimating the economic burden attributable to online only child sexual abuse offenders: implications for police strategy - Giles, Susan; Alison, Laurence; Humann, Michael; Tejeiro, Ricardo; Rhodes, Hayley (Frontiers in Psychology, 2024)
Evidence is beginning to emerge of the serious negative effects online only child sexual abuse (OOCSA) can have on victims. Establishing the scale and nature of the problem could assist police in prioritizing suspects. In study 1, scoping review identified eleven studies that examined OOCSA's impact on victims. Five themes emerged from narrative review; definitional issues, a new normal, OOCSA grooming processes, comparisons with offline CSA, mechanisms between OOCSA and harm. In study 2, OOCSA national prevalence was estimated by applying 2.9% rate of OOCSA observed from original police data to a lower bound (“sexual communication with a child” crimes recorded by the police), middle (scaling up to estimate undetected offenses) and upper bound estimate of the national offender pool (self-reported sexual solicitation offenders). Recent UK Home Office figures were adapted to establish economic costs. Lifetime costs estimates attributable to OOCSA are £7.4 million (police reports), £59.6 million (including undetected offenders) and £1.4 billion (national prevalence estimates). Over 75% of this is non-financial costs borne by victims in terms of emotional harm and lost output. Government bears around 20% of the cost burden, mostly non-financial costs for police forces. Findings are discussed in relation to evidence-led recommendations for prioritization and wider police actions that can be taken to avoid the considerable economic and social burden associated with OOCSA offenses.